Cooking and Sun Drying Effects on Properties of Allanblackia stanerana Kernels' Oil. (28th May 2014) - Noumi, Guy Bertrand; Pengou, Martin; Ngameni, Emmanuel
Abstract: Previous studies have evaluated the nutritive potential of Allanblackia oils. Oil extraction from Allanblackia is done after a pretreatment of the kernels which has an influence on oil quality. In Cameroon, the pretreatment consists of cooking, followed by drying of the almonds in the sun. The oil is either edible or used as a body cream. Because of these important applications, it is necessary to determine treatment conditions that maximize extraction yields and preserve its quality. This study was aimed at finding the mathematical models that simulate the best pre‐treatment conditions. The use of multiple linear regression analysis allowed developing satisfactory models and surface response plots that predict the evolution of the extraction rate as well as the quality of the extracted oil, depending on cooking and sun drying times. The coefficients of correlation obtained were 72.03 % for water content; 53.06 % for extraction yield; 71.06 % for acid; 76.48 and 83.29 % for iodine and refractive values respectively, indicating a suitable model of the experiment according to the studied variables. The response surface curves were superimposed to obtain a single optimal range that satisfies all response factors. The average cooking time of 12.5 min and the mean residence time of 8.5 days drying gave the following optimal values for the different response factors studied: moisture content 21.60 %; oil yield 70.69 %; refractive index 1.4546; iodine value 34.72; and acid value 0.38 mg KOH/g oil. The conditions to obtain a maximum extraction yield and low acidity were those that gave a residual water content of about 10–15 %. The quality indicators measured in this work generally remained within the threshold.